Screening Social Anxiety in Adolescents Through the Eyes of Their Carers - Garcia-Lopez, Luis-Joaquin; Espinosa-Fernandez, Lourdes; Muela-Martinez, Jose-Antonio; Piqueras, Jose Antonio (Frontiers in Psychology, 2021)
Despite the availability of efficacious treatment and screening protocols, social anxiety disorder (SAD) in adolescents is considerably under-detected and undertreated. Our main study objective was to examine a brief, valid, and reliable social anxiety measure already tested to serve as self-report child measure but administered via Internet aimed at listening to their parent’s ability to identify social anxiety symptomatology in their children. This parent version could be used as a complementary measure to avoid their children’s overestimation of social anxiety symptomatology using traditional self-reported measures. We examined the psychometric properties of brief and valid social anxiety measure in its parent format and administered via the Internet. The sample included 179 parents/legal guardian of adolescents (67% girls) with a clinical diagnosis of SAD (mean age: 14.27; SD= 1.33). Findings revealed good factor structure, internal consistency and construct validity. Data support a single, strength-based factor on the SPAIB-P, being structure largely invariant across age and gender. The limited number of adolescents with performance-only specifier prevented examining the utility of scale to screen for this recently established specifier. It is crucial to evaluate if these results generalize to different cultures and community samples.The findings suggest that the SPAIB-P evidences performance comparable with child-reported measure. Parents can be reliable reports of the adolescent’s social anxiety symptomatology. The SPAIB-P may be useful for identifying clinically-disturbed socially anxious adolescents.